Specific Features Of The Development Of Acmeology Culture In Future Teachers (Eurasian Journal of Learning and Academic Teaching, 2026)
The article focuses on the content and essence of the transformation of academic knowledge in the process of higher education, modern requirements for the content of training courses, scientific and theoretical foundations of the development of academic knowledge, pedagogical conditions for the development of academic knowledge in future training courses, structural components of academic knowledge, and the development and implementation of a functional framework for the development of academic knowledge in future training courses